2018
DOI: 10.1016/j.ijscr.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Silastic band erosion in the bypassed stomach after Fobi-Pouch operation for obesity: Case report

Abstract: HighlightsAccess to the excluded stomach in patients who have undergone a laparoscopic Roux-en-Y gastric bypass for evaluation and/or management remains a clinical concern.In order to facilitate the entrance to the gastric remnant, a silastic marker is left in place during the Fobi-Pouch operation.We report the first case of a patient presenting with an eroded silastic marker in the excluded stomach after a Fobi-Pouch operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…As far as we are aware there is only one case report published of erosion and bleeding caused by silastic rings. The case described by Franco-Martinez et al showed erosion of a ring into the bypassed stomach of a patient who had a Fobi-pouch operation, a variation to the Roux-en-Y gastric bypass, requiring resection of the stomach [9]. In our case we were able to avoid resection and the greater morbidity associated with it.…”
Section: Discussionmentioning
confidence: 47%
“…As far as we are aware there is only one case report published of erosion and bleeding caused by silastic rings. The case described by Franco-Martinez et al showed erosion of a ring into the bypassed stomach of a patient who had a Fobi-pouch operation, a variation to the Roux-en-Y gastric bypass, requiring resection of the stomach [9]. In our case we were able to avoid resection and the greater morbidity associated with it.…”
Section: Discussionmentioning
confidence: 47%